Karl Kraus und Peter Altenberg : Eine Typologie moderner Haltungen - Ganahl, Simon 1981- (Konstanz University Press, 2015)
The book explores the modern attitudes that are articulated in the texts "Third Walpurgis Night" (1933) by Karl Kraus and "Prodromos" (1905) by Peter Altenberg. Following Foucault's discourse analytical approach and his concept of self practice, it asks with what types of subject and truth the two literary works break open the structures of enunciation in which they are historically embedded. The result is not a biographical or philological comparison, but a report on the experience of a performative reading that makes an archaeological section of the writings and reconstructs their genealogical line